A new species of Trimma of the T. taylori species group (Teleostei: Gobiidae) from the Red Sea, Indian Ocean - Winterbottom, Richard; Bogorodsky, Sergey V.; Alpermann, Tilman J. (Zootaxa, 2023)
A new species of Trimma is described from the Red Sea along the Saudi Arabian coast. Specimens and/or photographs of this species are available from the Egyptian Red Sea to Eritrea. These specimens, formerly identified as T. taylori, differ from all other samples from the Indo-Pacific currently identified as T. taylori in having 9 and 8–9 dorsal- and anal-fin rays respectively (vs. usually 10 and 10 rays), 13 pectoral-fin rays (vs. usually 14 rays), and cycloid scales covering the entire predorsal region from the upper base of the pectoral fin anterior to a convex line posterodorsally to just lateral to the base of the sixth first dorsal-fin spine (vs. predorsal region mostly or entirely covered with ctenoid scales). In addition, specimens from the Red Sea form a monophyletic lineage in a Maximum Likelihood analysis of the COI gene. In this tree, the new species is the sister group to a clade composed of three lineages. One is composed of specimens from the Maldives, which is the sister group of a single available specimen from the Seychelles. These two together are the sister group of specimens of a widespread western Pacific clade.